Temporal and Spatial Characteristics of Soil Erosion in Typical Counties of Black Soil Region Based on RUSLE - Wang Ting; Lu Zhongjun; Ning Jing; Fu Bin; Xin Rui; Huang Nan; Zhao Bowen (Shuitu baochi tongbao)
[Objective] The spatiotemporal characteristics of soil erosion were analyzed in order to provide a reference for soil erosion control and evaluation of soil and water conservation benefits. [Methods] Based on the RUSLE soil erosion equation, the spatial-temporal evolution of soil erosion in the typical black soil region of Binxian County, Heilongjiang Province from 2000 to 2020 was analyzed with the support of RS and GIS. The effects of topographic factors and land use on soil erosion were also investigated. [Results] ① The average modulus of soil erosion in 2000, 2010, and 2020 was 893.02 t/(km2·yr), 499.84 t/(km2·yr), and 1 561.02 t/(km2·yr), respectively. The soil erosion intensity was mainly classified as slight and mild. ② The low intensity erosion was distributed across the entire region, and the high intensity erosion was mainly located in the southern mountainous area. ③ Erosion mainly occurred at elevations of 100 to 200 m. Soil erosion area was inversely proportional to slope. 0°—5° slope was the main erosion gradient zone. Soil erosion area in the direction of the north slope was larger than in the direction of the south slope; ④ The soil erosion modulus and the area of sloping farmland in the study area were larger. This area is the key area for soil erosion control in Binxian County, Heilongjiang Province. [Conclusion] From 2000 to 2020, the average soil erosion modulus initially increased and then decreased, showing a significant spatiotemporal differentiation. Topographic factors and land use change had significant driving effects on soil erosion in the study area. It can be used as a reference for soil erosion control and soil and water conservation benefit evaluation in black soil region.